Underground coal minig - global picture and brief overview - Fuginski, Zygmunt (2021)
Underground mining currently accounts for a bigger share of world coal production than opencast • About 60% from the total production is from underground mines • In several major coal producing countries surface mining is more common. For example, surface mining accounts for around 80% of production in Australia; • In the USA it is used for about 30% of production.